Figurinos em Persona: a narrativa visual em perspectiva - Rodor, Alana Victoria (Revista do Colóquio, 2023)
In this article the exposure and analysis of the costumes through the acts ofthe movie “Persona” (1966), by Ingmar Bergman, is done to comprehend how theywork in conformity with its narrative. Considering their importance in characterizingthe characters and the history, in which their identities slowly merge, it is shown thatthe costumes also change as the narrative evolves, and they work to enhance it.